RESPON PETANI TERHADAP APLIKASI DIAGNOSA HAMA PENYAKIT DAN PENGENDALIAN BAWANG MERAH BERBASIS WEB (STUDI KASUS PETANI BAWANG MERAH DI BREBES DAN CIREBON) - Aditiameri dan Rini Setyowati (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2019)
he development of information and communication technology from day to day is increasing and growing widely ranging from urban areas to rural areas. Farmers can utilize information and communication technology to know various information about the world of agriculture, how to cultivate good crops, to how to overcome and cope with various types of plant diseases. Red onion plants can be attacked by various pests and diseases. Pests and diseases can be known from the symptoms caused, but to know exactly the type of pests and diseases that attack the onion plants requires an expert / agri-cultural expert. While the number of agricultural experts is limited and can not solve the problems of farmers at the same time, so it takes a system that has the ability as an expert, which in this system contains expertise of an agricultural expert about pests and symptoms of onion plants. To find out how far onion far-mers can receive expert pest disease diagnosis system and web-based control must be known social and economic of local farmers. The determination of the research location by using purposive sampling method with the consideration of Ketanggungan District - Brebes and Losari District is the biggest development area of shallot onion in Central Java and West Java. Research on each of 50 farmer respondents in each location was done by filling and interviewing the respondent's farmers selected by convenience sampling (most easily found) in the field. Characteristic in the form of age, education level, farm experience, land area and land ownership affect farmers skills in managing the onion crop busi-ness. Karateritik farmers also affect the level of acceptance of farmers in adopt-ing new technology in the form of expert systems of pest and disease diagnosis plant red onion web-based. High-educated farmers faster adoption, while low-educated farmers more difficult to accept new technologies. From the results of the research, the level of education onion farmers in Kecamatan Ketanggungan Brebes and District Losari Cirebon many low-educated elementary school that is 58% and 56%. . Land ownership and narrowness of land arable significant ef-fect on funding limitations, so the onion farmers in Tanggungan - District, Brebes and Subari Losari Cirebon which has a little android phone (≥95%) so that few farmers can access web-based expert system. Keywords: expert system, pest diagnosis, shallot plant, socio-economic charac-teristics of farmers